(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: to find out the accuracy of CT scan in diagnosing retinoblastoma with the gold standard of diagnosis being histopathology. Study design: It is a cross sectional study Done in the department of diagnostic radiology, Lahore general hospital, Lahore from 02-05-2013 to 01 -11 -2013. Patients and Methodology: This study comprised of 240 patients with clinical suspicion of retinoblastoma. Computed tomography on Toshiba Asteion VF Model TXS 021B/1N, Single Slice Helical, images in the axial, sagittal and coronal projections was obtained without l/V contrast. The cases were operated and histopathological results were recorded. The results of computed tomography and histopathology were compared taking histopathology as gold standard. Results: Out of 240 patients, 135 patients (56.25%) had retinoblastoma computed tomography. After comparison of results of computed tomography with histopathology, the sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of computed tomography were 87.14%, 90.48%, 92.19%, 84.82% and 88.75% respectively. Conclusion: CT scanning with a sensitivity of 87.14% and a specificity of 90.48% in the diagnosis of retinoblastoma should be considered a worthwhile modality. It provides an edge in diagnosis with its accurate depiction of even the smallest calcifications. The earlier the detection, the earlier will be the treatment and its effectiveness.